Living through the Hoop : High School Basketball, Race, and the American Dream. - May, Reuben A. Buford A. Buford (NYU Press, 2007)
Visit the author's YouTube channel!. When high school basketball player LeBron James was selected as the top pick in the National Basketball Association draft of 2003, the hopes of a half-million high school basketball players soared. If LeBron could go straight from high school to the NBA, why couldn't they? Such is the allure of basketball for so many young African American men. Unfortunately, the reality is that their chances of ever playing basketball at the professional, or even college, level are infinitesimal. In Living Through the Hoop, Reuben A. Buford May tells the absorbing story o.